Contextual Interpretation Method: Epistemological and Methodological Study and Its Implementation in Current Issues - Nur Aisyah; Muhith Marzuki (al-Afkar, Journal For Islamic Studies, 2026)
This study critically examines the epistemology, methodology, and implementation of contextual interpretation (tafsir kontekstual) in contemporary Qur'anic studies. Employing a qualitative approach with library research method, this study analyzes the thoughts of four key figures Fazlur Rahman with his double movement theory, Abdullah Saeed with his systematization of value hierarchy and structured interpretive steps, Hassan Hanafi with his engagement hermeneutics and transformative interpretation, and Sahiron Syamsuddin with the Ma'na Cum Maghza method as a local innovation from the Indonesian archipelago. The findings reveal that all four scholars share a common thread: the rejection of literal-textual readings and the recognition of the role of context in meaning-making, although they differ in their starting points of interpretation and operational steps. The implementation of this method on contemporary issues such as gender equality, religious tolerance, and socio-economic justice has proven capable of providing alternative interpretations that are more humane and progressive. However, this study also identifies theoretical and practical challenges, including criticism from traditionalist circles regarding the risks of relativism and erosion of textual authority, as well as implementational problems within Muslim communities that still strongly adhere to classical interpretations. Theoretically, this study strengthens the argument that contextual interpretation is a natural continuation of the maqasid al-shari'ah principle and the tradition of ijtihad, while practically, the results of this study can serve as a reference for exegetes, lecturers, and students in developing contextual and anticipatory interpretive strategies responsive to contemporary dynamics. The limitations of this study lie in the data sources being restricted to English and Indonesian literature, not yet including Arabic or Persian sources, as well as the lack of empirical testing of the implementation of contextual interpretation in specific Muslim communities.